Evaluating Bang for the Buck: A Cost-Effectiveness Comparison Between Individual Interviews and Focus Groups Based on Thematic Saturation Levels. (September 2016) - Namey, Emily; Guest, Greg; McKenna, Kevin; Chen, Mario
Evaluators often use qualitative research methods, yet there is little evidence on the comparative cost-effectiveness of the two most commonly employed qualitative methods—in-depth interviews (IDIs) and focus groups (FGs). We performed an inductive thematic analysis of data from 40 IDIs and 40 FGs on the health-seeking behaviors of African American men ( N = 350) in Durham, North Carolina. We used a bootstrap simulation to generate 10, 000 random samples from each data set and calculated the number of data collection events necessary to reach different levels of thematic saturation. The median number of data collection events required to reach 80% and 90% saturation was 8 and 16, respectively, for IDIs and 3 and 5 for FGs. Interviews took longer but were more cost-effective at both levels. At the median, IDIs cost 20–36% less to reach thematic saturation. Evaluators can consider these empirically based cost-effectiveness data when selecting a qualitative data collection method.